Efficient Photoacoustic Imaging With Biomimetic Mesoporous Silica-Based Nanoparticles - Huang, Chuangjia; Guan, Xiaoling; Lin, Hui; Liang, Lu; Miao, Yingling; Wu, Yueheng; Bao, Huiqiong; Wu, Xiaodan; Shen, Ao; Wei, Minyan; Huang, Jionghua (Frontiers in Bioengineering and Biotechnology, 2021)
Indocyanine green (ICG), a near-infrared (NIR) fluorescent dye approved by the Food and Drug Administration (FDA), has been extensively used as a photoacoustic (PA) probe for PA imaging. However, its practical application is limited by poor photostability in water, rapid body clearance, and non-specificity. Herein, we fabricated a novel biomimetic nanoprobe by coating ICG-loaded mesoporous silica nanoparticles with the cancer cell membrane (namely, CMI) for PA imaging. This probe exhibited good dispersion, large loading efficiency, good biocompatibility, and homologous targeting ability to Hela cells in vitro. Furthermore, the in vivo and ex vivo PA imaging on Hela tumor-bearing nude mice demonstrated that CMI could accumulate in tumor tissue and display a superior PA imaging efficacy compared with free ICG. All these results demonstrated that CMI might be a promising contrast agent for PA imaging of cervical carcinoma.